PEREMPUAN DAN POLITIK, DIKOTOMI ANTARA RUANG PRIVAT DAN RUANG PUBLIK (Studi Kasus Anggota Legislatif Terpilih DPRD Kota Tasikmalaya Periode 2009-2014) - Edi Kusmayadi; Wiwi Widiastuti; Fitriyani Yuliawati (Jurnal Ilmu Politik dan Pemerintahan, 2011)
The study, entitled Women and Politics, The dichotomy between private space and the Public Sphere (Case Study Elected Member of Parliament Legislative Tasikmalaya Period 2009-2014). This study aims to determine the extent of women sitting in parliament to create gender-equitable policies among the dichotomy between the private and public spaces. The method used is a qualitative methodology, with the technique of informants using purposive sampling. Data collection through in-depth interviews and observation. The analytical method used is a triangulation of sources. It can be concluded that the City Assembly Members Tasikmalaya despite a 30% quota has not been represented, but in the presence of women legislators in the town of Tasikmalaya, had proved that the public and private roles of women can be done hand in hand and prove that women can become members of parliament sitting and can make policy based on justice among gender dichotomy between the private and public spaces.